Computational modelling for the spiral flow in umbilical arteries with different systole/diastole flow velocity ratios. (October 2020) - Wen, J.; Tang, J.; Ran, S.; Ho, H.
Highlights: A first simulation has been made for the spiral flows under different systole/diastole ratios and ultrasonic velocity waveforms. Simulation results show that coils enhance the wall shear stress with the same velocity waveform. High systole/diastole ratios generate a up to 62% wall shear gradient in the same cross section. Time averaged WSS are generally increased and more uneven in the hyper-coiling model. Such a high shear stress gradient may contribute to the chirality of umbilical arteries. Abstract: The systole/diastole (S/D) flow velocity ratios in umbilical arteries (UAs) have been used to assess the health status of the feto-placental circulation, yet its connection to the morphology of UAs, specifically its coiling pattern remains unclear. Spiral flow induces unbalanced wall shear stress (WSS) distribution in UAs, and may contribute to the uneven arterial wall thickness, and the chirality. In this paper, we use a 3D computational fluid dynamics (CFD) technique to quantify the wall shear stress (WSS) in UA models of two configurations, i.e. at 0.17 and 0.50 spirals per centimeter, to represent normo- and hyper-coiling, respectively. For CFD simulations we use two different S/D ratios (3.02 and 5.70) revealed from the ultrasonography waveforms of a normal and an intrauterine growth restriction (IUGR) case. We found that more coils in the UA model enhanced WSS throughout a cardiac cycle (up to 24%) with the same inflow condition. In addition, time-averaged WSS are generally increased and more uneven in the hyper-coiling model. We suggest that the large WSS difference between the peak systole and end diastole (62% higher in the IURG case than the normal case) may induce uneven stenosis distribution at UAs, and contribute to UA chirality.